Systems Biology to Understand and Regulate Human Retroviral Proinflammatory Response - Helmy, Mohamed; Selvarajoo, Kumar (Frontiers in Immunology, 2021)
The majority of the human genome is non-coding genes. Recent research have revealed that about half of these genome sequences make up transposable elements. A branch of these belongs to the endogenous retroviruses (ERVs), which are germline viral infections that occurred millions of years ago. They are generally harmless as evolutionary mutations have made them unable to produce viral agents and are mostly epigenetically silenced. Nevertheless, ERVs are able to express by still unknown mechanisms and recent evidence has shown causalities between ERVs and major proinflammatory diseases and cancers. The major challenge is to elucidate a detailed mechanistic link between them, so that novel therapeutic approaches can be explored. Here, we provide a brief overview of the human ERVs and their roles in Toll-like receptor induced innate immune response, and the possible link to cancer. Finally, we recommend the employment of systems biology approaches for future HERV research.